Targeting Ischemia-reperfusion injury in liver transplant rejuvenation - Kenneth J. Dery; Fady Kaldas; Jerzy W. Kupiec-Weglinski (Transplantation Reports)
Background: Hepatic ischemia-reperfusion injury (HIRI) is a multifaceted pathophysiological process involving a cascade of interconnected cellular events. The initial ischemic stress, followed by the reestablishment of blood circulation to the liver, triggers a feed-forward innate immune-driven response that exacerbates the hepatocellular injury. HIRI poses a significant clinical challenge in liver transplantation (LT), as it can result in tissue damage, organ dysfunction, and poor clinical outcomes. Methods and results: This review highlights current key issues in HIRI translational research, as revealed by recent bibliometric studies. It examines the mechanisms that facilitate homeostatic regulation after HIRI. Additionally, it addresses refined pharmacological strategies aimed at mitigating oxidative stress and inflammation. Hot topic areas in HIRI research include autophagy, donation after circulatory death, and NLRP3-dependent inflammasome activation following LT. New pharmacological agents, such as anti-oxidative compounds, metabolic modulators, and plant-derived compounds, are being explored to influence inflammatory responses. There is a strong clinical emphasis on broadening the donor pool by utilizing marginal donor grafts and advanced machine perfusion techniques. Enhancing translational research through the development of human-relevant organoids or ex vivo liver perfusion systems is essential for connecting laboratory discoveries with clinical practices in life-saving surgical procedures. Conclusion: A comprehensive approach that emphasizes the regulatory mechanisms of cellular responses to oxygen stress and immune cell activation, alongside innovative donor organ preservation, like machine perfusion, will shape the future direction of HIRI research by enhancing graft viability and revitalizing suboptimal donor organs.